2020
DOI: 10.14295/bds.2020.v23i4.2072
|View full text |Cite
|
Sign up to set email alerts
|

Microtensile Bond Strength and Failure Type Analysis of Self-Etch Adhesive Systems on Superficial and Deep Dentin After Long-term Water Storage

Abstract: Objective: The aim of this study was to evaluate and compare the microtensile bond strengths of four current adhesive materials that contain different monomers at deep and superficial dentin. Material and Methods: Forty non-carious human third molars (n = 5) were used in the study. Specimens were divided into two main groups according to dentin thickness as superficial and deep dentin. Groups were further divided into four subgroups in terms of the adhesive systems used: Nova Compo B Plus (NCBP), Nova Compo B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…The organic solvent of some bonding systems may be diluted by this water, leading monomers to exit the soluble phase and form resin globules in the solution. The hydrophilicity of the adhesive system to superficial dentin and highly acidic monomers that are able to form strong ionic interactions with dentin's calcium content are the reasons Cevik P et al, 2020 20 found greater μTBS to shallow dentin surface than to deep dentin surface. Deep dentine's decreased binding strength can be explained by…”
Section: Discussionmentioning
confidence: 99%
“…The organic solvent of some bonding systems may be diluted by this water, leading monomers to exit the soluble phase and form resin globules in the solution. The hydrophilicity of the adhesive system to superficial dentin and highly acidic monomers that are able to form strong ionic interactions with dentin's calcium content are the reasons Cevik P et al, 2020 20 found greater μTBS to shallow dentin surface than to deep dentin surface. Deep dentine's decreased binding strength can be explained by…”
Section: Discussionmentioning
confidence: 99%
“…However, Clearfil S3 Bond did not provide a reliable bond strength compared with the other two adhesives, which can be related to its functional monomers. Cevik et al [ 31 ] reported that self-etch adhesives containing MDP and 4-methacryloyloxyethyl trimellitate anhydride showed more favorable bond strength to dentin compared with other types [ 31 ]. The result of their study was in accordance with our study as G-Premio Bond containing the afore-mentioned monomers showed higher bond strength to dentin in comparison with two other groups.…”
Section: Discussionmentioning
confidence: 99%